What Do We Know About the Winchester House? - Berne, Emma Carlson, 1979-; Hammond, Ted (New York : Penguin Workshop, 2023)
"In 1884, Sarah Winchester began building a large mansion in Santa Clara County, California. Under Sarah's direction, the house rose to be seven stories high and filled with mysterious features, including stairs that lead to nowhere and windows that look into other interior rooms. The house is more than just oddly designed, however: Many people believe that it is haunted. What made the heiress to the Winchester rifle fortune, an independent woman in many ways ahead of her time, create such an unusual house? Is it really filled with ghosts and spirit energy? Find out more in this nonfiction title about one of America's most famously unexplainable and possibly haunted houses"--.
new kids book 2023 fall.
Includes bibliographical references.
Ages 8-12
Keywords: Winchester, Sarah Pardee, -- 1837-1922 -- Homes and haunts -- California -- San Jose -- Juvenile literature; Winchester Mystery House (San Jose, Calif.) -- Juvenile literature; Ghosts -- Juvenile literature -- California -- San Jose; Haunted houses -- Juvenile literature -- California -- San Jose